Inequality in Germany: Decrease in gap for gross hourly wages since 2014, but monthly and annual wages remain on plateau - Markus M. Grabka; Carsten Schröder (DIW Weekly Report, 2018)
Despite the booming German labor market, wage inequality is still a relevant issue. In the present study, the authors report on the changes in wages and their distribution between 1992 and 2016. In addition to real contractual gross hourly wages, we closely examined gross monthly and annual wages. Based on Socio-Economic Panel (SOEP) data, the results show that wage inequality rose significantly between 1992 and 2005, in particular with respect to monthly and annual wages. Since then inequality in monthly and annual wages has plateaued at its 2005 level. Inequality in hourly wages has decreased only since 2014, and between 2013 and 2016, average real gross hourly wages rose by five percent after a longer phase of stagnation. For the lowest ten percent of the population, they rose by 13 percent-a rate related to the implementation of sector-specific wages and the statutory minimum wage. However, these minimum wages obviously did not affect monthly and annual wages as anticipated.
Keywords: D31; I31; I32; 330; wage inequality; monthly earnings; annual earnings; SOEP